Public spending and the role of the state : history, performance, risk and remedies - Schuknecht, Ludger, 1962- (New York : Cambridge University Press, 2021)
"Public expenditure is an essential tool for governments to underpin prosperity, opportunities and freedom in our advanced countries. But discontent is spreading at a time when high spending, debt and new challenges risk overwhelming many governments. This book's four themes are, therefore, as relevant today as they are timeless: 1) The role of the state has grown enormously over the past 150 years, initially setting sound rules of the game and providing essential public goods and services. In recent decades, however, public spending has often grown more than needed and lost focus, while public debt has reached record levels. 2) There are huge differences in the 'value for money' citizens get from their governments. Public spending of 30%-35% of GDP, or perhaps 40%, suffices to do well, which is much less than the prevailing 45%-55% in many countries. 3) There are dark clouds on the horizon from risks in the social and financial sphere. If social spending trends continue, or if a new financial crisis strikes, public finances will not be sustainable in many countries. 4) Governments need to reform their expenditure and strengthen their rules and institutions to deliver better on their core tasks. This way, they will stay lean, efficient and sustainable"--
Includes bibliographical references and index.
Keywords: Expenditures, Public; Government spending policy; Financial services industry -- Government policy; Social policy